Simple and Selective HPLC-UV/Vis Bioanalytical Method to Determine Aluminum Phthalocyanine Chloride in Skin Permeation Studies - Thaiene Avila Reis; Ana Elise Jaculi; Rubens da Costa Alves; Tais Gratieri; Ricardo Bentes Azevedo; Graziella Anselmo Joanitti; Guilherme Martins Gelfuso; Marcilio Cunha-Filho (Journal of Analytical Methods in Chemistry)
Considering the feasibility of the aluminum phthalocyanine chloride (AlPcCl) application in the topical photodynamic therapy of cutaneous tumors and the lack of HPLC methods capable of supporting skin permeation experiments using this compound, the aim of this study was to obtain a simple and selective chromatographic method for AlPcCl determination in skin matrices. A HPLC-UV/Vis method was developed using a normal-phase column operating at 30°C, an isocratic mobile phase of methanol : phosphoric acid (0.01 M) at 1.5 mL/min, and detection at 670 nm. The method exhibited (i) selectivity against various contaminants found in the different skin layers, (ii) high drug extraction capacity from the hair follicle (>70%) and remaining skin (>80%), and (iii) low limits of detection and of quantification (0.03 and 0.09 μg/mL, resp.). The method was also linear in the range from 0.1 to 5.0 µg/mL (r = 0.9994) and demonstrated robustness with regard to experimental chromatographic parameters according to a factorial design. Lastly, the developed method was successfully tested in in vitro skin permeation studies of AlPcCl, proving its effectiveness in the development of pharmaceutical delivery systems containing this drug for topical photodynamic therapy of skin cancers.